Performance of Three Popular Statistical Softwares in Generating Random Numbers - Musa, Luqman Hakim; Adam, Mohd Bakri (Institute for Mathematical Research, 2009)
Random numbers are essential ingredients in a statistical analysis, They can be generated easily through statistical software packages, Each statistical package varies in terms of performance. Our objective is to compare the performances of three statistical software packages, namely R, SAS and SPSS based on their accurateness and time consumption in generating and analyzing random numbers. We obtain some estimated statistics to assess their accuracies. Comparison of the times in generating the random numbers is also observed.